Library classification trends in the 21st century - Kumbhar, Rajendra; Alonso, A.; ScienceDirect eBooks (Witney : Chandos Publishing (Oxford) Ltd, 2012)
This book traces development in and around library classification as reported in literature published in the first decade of the 21st century. It reviews literature published on various aspects of library classification including modern applications of classification such as internet resource discovery, automatic book classification, text categorization, modern manifestations of classification such as taxonomies, folksonomies and ontologies and interoperable systems enabling crosswalk. The book also features classification education and an exploration of relevant topics.
Knowledge organisation and knowledge organisation systems -- Classification and its uses -- Construction of classification schemes -- General classification schemes -- Special classification schemes and classification of non-bibliographic entities -- Automatic book classification, reclassification and non-classificatory approaches to knowledge organisation -- Classification education -- Modern knowledge organisation systems and interoperability -- Text categorisation -- Classification: theories, research trends and personalities.
Includes bibliographical references (pages 143-170) and index.
Elsevier
Safari Books Online
Keywords: Classification -- History -- 21st century; Information organization -- History -- 21st century; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Classification; Information organization; 2000-2099; Electronic books